First report of the genus Kohliella Brauns, 1910 (Hymenoptera: Crabronidae: Crabroninae) from India with the species K. anula Pulawski, 1991 from Kerala - Mawadda, N.v. Ayisha; Kumar, P. Girish; Sureshan, P.m. (Zootaxa, 2020)
The digger wasp genus Kohliella Brauns, 1910, a member of the tribe Larrini, subfamily Crabroninae of the family Crabronidae, is a rarely occurring genus comprising only three known species worldwide (Pulawski 1991; 2020). The genus has been recorded from the Ethiopian (South Africa and Zimbabwe; two species) and Oriental (Sri Lanka; one species) regions. Brauns (1910) erected the genus based on the type species Kohliella alaris from South Africa. The genus is characterized by a V-shaped swelling on the frons, an oblong tubercle on the mandible and a petiolate third submarginal cell of the forewing (Bohart & Menke 1976; Pulawski 1991). The nesting habits are known only for Kohliella alaris. Gess and Gess (1980) studied the life history of this species. It preys on nymphal tree cricket Oecanthus filiger Walker, and nests in the ground in flat, sandy areas with sparse vegetation; nests are constructed prior to hunting. In this paper, Kohliella anula Pulawski, 1991, previously known from Sri Lanka only, is recorded for the first time from India.